(untitled) (Journal of Health, Population and Nutrition, 2010)
Morbidity and mortality data are important for planning and implementing healthcare strategies of a country. To understand the major causes for hospitalizations in rural Bangladesh, demographic and clinical data were collected from the hospital-records of five government-run rural health facilities (upazila health complexes) situated at different geographical regions of the country from January 1997 to December 2001. During this period, 75,598 hospital admissions in total were recorded, of which 54% were for male, and 46% were for female. Of all the admissions, diarrhoeal disease was the leading cause for hospitalization (25.1%), followed by injuries (17.7%), respiratory tract diseases (12.6%), diseases of the gastrointestinal tract (10.5%), obstetric and gynaecological causes (8.5%), and febrile illnesses (6.7%). A considerable proportion (8.3%) of the hospitalized patients remained undiagnosed. Despite the limitations of hospitalbased data, this paper gives a reasonable insight of the important causes for hospitalizations in upazila health complexes that may guide the policy-makers in strengthening and prioritizing the healthcare needs at the upazila level in Bangladesh. Key words: Hospitalization; Morbidity; Rural health services; Bangladesh DOI: 10.3329/jhpn.v28i4.6047 J HEALTH POPUL NUTR 2010 Aug;28(4):399-404